Automatic PLC Control Logic Generation Method Based on SysML System Design Model - Bo Ling; Changyong Chu; Chuan Xu (Actuators)
Automatic generation of Programmable Logic Controller (PLC) programs from system design models can reduce system development costs and shorten system development cycles. However, effective methods for ensuring the quality and performance of control logic automatically generated from system design models are still lacking. This paper proposed a model-driven PLC program automatic generation approach. Firstly, a clear formal specification for the system design model oriented to PLC programming was established. Secondly, the fundamental semantic correspondence between system model elements and PLC program elements was defined by devising a set of mapping rules. Thirdly, a novel mapping algorithm was proposed to generate a PLC program based on system design models. Finally, an example of the automatic generation of a PLC control program for a handling robot was used to verify the effectiveness of the method. This method can provide system-level design and analysis capabilities during the initial stages of model development, offering solutions to the challenges of complexity modeling and engineering efficiency. Additionally, it is expected to have wide-ranging applications in the industrial automation sector, thereby contributing to the innovation and advancement of automation systems.